2011
DOI: 10.1377/hlthaff.2011.0196
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Links Increases In Public Health Spending To Declines In Preventable Deaths

Abstract: Public health encompasses a broad array of programs designed to prevent the occurrence of disease and injury within communities. But policy makers have little evidence to draw on when determining the value of investments in these program activities, which currently account for less than 5 percent of US health spending. We examine whether changes in spending by local public health agencies over a thirteen-year period contributed to changes in rates of community mortality from preventable causes of death, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(181 citation statements)
references
References 45 publications
10
167
1
3
Order By: Relevance
“…These include, notably, the Public Health Activities and Services Tracking (PHAST) study, Bernet's database of Florida LHD spending since 2000, the Public Health Uniform National Data System (PHUND$; http://phunds.naccho.org/), and Brown's database of California LHD spending (11,14,18,83). Brown has published numerous seminal studies using these data to examine the value of local public health spending, whereas Mays has used NACCHO data to examine similar issues (18,70,93). These data sets continue to demonstrate substantial variety in local public health 478 Leider et al spending across the United States, driven largely by the extent of LHD public health activity (high/medium/low capacity), as well as by the level of clinical services provided by the LHD.…”
Section: Specialty Estimates Of Lhd Spendingmentioning
confidence: 99%
“…These include, notably, the Public Health Activities and Services Tracking (PHAST) study, Bernet's database of Florida LHD spending since 2000, the Public Health Uniform National Data System (PHUND$; http://phunds.naccho.org/), and Brown's database of California LHD spending (11,14,18,83). Brown has published numerous seminal studies using these data to examine the value of local public health spending, whereas Mays has used NACCHO data to examine similar issues (18,70,93). These data sets continue to demonstrate substantial variety in local public health 478 Leider et al spending across the United States, driven largely by the extent of LHD public health activity (high/medium/low capacity), as well as by the level of clinical services provided by the LHD.…”
Section: Specialty Estimates Of Lhd Spendingmentioning
confidence: 99%
“…The contribution of medical care to premature mortality (10%) is less important than social circumstances (15%), genetic predisposition (30%), and behavioral patterns (40%.) 32 Public health spending, currently less than 5% of national health spending, is the strongest mutable determinant of community-level preventable mortality (increasing public health spending significantly decreases infant death and death from heart disease, diabetes, and cancer 33 ). Constrained resources demand more effective allocation.…”
Section: Reinvigoration Of the Folsom Report: Why Hope? Why Now?mentioning
confidence: 99%
“…Communities governed by a local board of health show increased public health spending, likely because they can better identify funding targets. 33 Ideally, federal health policy would more effectively enable local community-based reform efforts. For example, accountable care organizations, introduced in the Affordable Care Act as a pilot program within the Centers for Medicare and Medicaid Services, are a potential modern-day Community of Solution, but are politically uncertain and too hospital-centric.…”
Section: Parallel Transformation and The Importance Of Community-basementioning
confidence: 99%
“…These gains can be attributed to a number of factors, including better education, nutrition, sanitation, housing as well as greater access to health services [4,5]. Several studies have confirmed that there is a positive relationship between life expectancy at birth and health expenditure per capita worldwide [6][7][8]. A recent study by Joumard [9] in 2010 showed that an increase of total health spending is the possible reason for at least 40% of improvements in life expectancy since 1990.…”
Section: Introductionmentioning
confidence: 99%